THE IMMUNE SYSTEM IN INFANTS: RELEVANCE TO XENOTRANSPLANTATION - Bikhet, Mohamed (Pediatr Transplant, 2020)
Despite the improvement in surgical interventions in the treatment of congenital heart disease, many life-threatening lesions (e.g., hypoplastic left heart syndrome) ultimately require transplantation. However, there is a great limitation in the availability of deceased human cardiac donors of a suitable size. Hearts from genetically-engineered pigs may provide an alternative source. The relatively immature immune system in infants (e.g., absence of anti-carbohydrate antibodies, reduced complement activation, reduced innate immune cell activity) should minimize the risk of early antibody-mediated rejection of a pig graft. Additionally, recipient thymectomy, performed almost routinely as a preliminary to orthotopic heart transplantation in this age group, impairs the T cell response. Because of the increasing availability of genetically-engineered pigs (e.g., triple knockout pigs that do not express any of the three known carbohydrate antigens against which humans have natural antibodies), and the ability to diagnose congenital heart disease during fetal life, cardiac xenotransplantation could be pre-planned to be carried out soon after birth. Because of these several advantages, prolonged graft survival and even the induction of tolerance, e.g., following donor-specific pig thymus transplantation, is more likely to be achieved in infants than in adults. In this review, we summarize the factors in the infant immune system that would be advantageous in the success of cardiac xenotransplantation in this age group.